The effectiveness of government promotion of advanced manufacturing technologies (AMT): An economic analysis based on Swiss micro data - Spyros Arvanitis; Heinz Hollenstein; Stephan Lenz (ETH Zurich, KOF Swiss Economic Institute, 2002)
This paper describes the approach applied and the results of an evaluation of the effects of the Swiss government programme to promote the diffusion of Advanced Manufacturing Technologies (AMT) from 1990 to 1996. The method used is based on specifying and econometrically estimating with firm data simultaneously an adoption equation which, besides the main explanatory variables as proposed by the theory of technology diffusion, includes a policy variable, and a policy equation with a set of firm characteristics and an adoption variable as regressors. The results are consistent with a positive impact of promotion on adoption of AMT, particularly a more intensive adoption of AMT for firms which did not use AMT when the programme started.
Keywords: 330; Innovationspolitik; Innovationsdiffusion; Schätzung; Schweiz